Habitats Characteristic and the Resistance Status of Aedes sp. Larvae in the Endemic Areas of Dengue Haemorrhagic Fever in Sewon Subdistrict, Bantul Regency, Special Region of Yogyakarta - Soenarwan Hery Poerwanto; Defriana Lutfi Chusnaifah; Giyantolin Giyantolin; Dila Hening Windyaraini (Journal of Tropical Biodiversity and Biotechnology, 2020)
Dengue Hemorrhagic Fever (DHF) is caused by Dengue Virus and transmitted by female Aedes mosquito which spread almost all over the world. Aedes sp. mosquito lives cosmopolitan and breeds in wet environments. Panggungharjo and Bangunharjo villages were categorized as endemic and non-endemic DHF areas, respectively. The aims of this research were to study the characteristics of Aedes sp. mosquito breeding sites, the identity of presence species found in the sites, and the resistance status of Aedes sp. mosquitoes against organophosphate insecticide. The method was using a larval survey which consists of 200 houses as respondents located in Panggungharjo and Bangunharjo villages. The larval resistance was tested by a biochemical method since resistance could be associated with esterase enzyme activity. The characteristics of mosquito breeding sites that found were open containers, filled with clear and calm water, dark and rough wall surfaces, the bottom surface was not directly in contact with the ground, the water temperature was 27-29 °C, pH 6.5-7, and not directly exposed to sunlight. There was only one species of mosquito was found, Aedes aegypti. The resistance test of Aedes sp. larvae showed that Aedes sp. larvae population from Panggungharjo village were susceptible, and Aedes sp. larvae from Bangunharjo village were in moderate resistant against organophosphate insecticide.